SIMULATION OF THE EFFECTS OF RIVERS AND SLUICES ON THE PROCESS OF SALTWATER INTRUSION IN THE MEKONG RIVER DELTA - Hoàng Ngọc Hiển; Ngô Đức Lưu; Huỳnh Xuân Hiệp (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, facing the reality of saltwater intrusion developments in the river and sluice system in the Mekong Delta region today, we propose new approaches by building models and modeling saltwater intrusion, based on the multi-agent technique and the simulation of Gama. Simulation of the effects of rivers and sluices on saltwater intrusion in the Mekong Delta region was tested on the basis of previous data and a proposed model was made. The simulation results were maps of saltwater intrusion associated with the river and sluice systems over time and statistics on the saltwater intrusion for administrative units. The results on degree of influence of saltwater intrusion were also evaluated compared to the reality for solutions to reduce losses due to saltwater intrusion and climate change.